El pensamiento complejo y el desarrollo de competencias transdisciplinares en la formación profesional - Estrada García, Alex (2018)
The aim of this article is to show the influence of the epistemology of complexity on the development of transdisciplinary competences, as well as to contextualize its development within the framework of the debate on the epistemological thinking of the country's education. The paradigm of complexity is a network of knowledge that unites scientists from different fields of knowledge who insist on the convenience of adopting new theoretical and methodological models and, therefore, a new epistemology of knowledge, which allows the scientific community to elaborate theories that are more adjusted to reality. The objective of these tasks is that the student can integrate knowledge, attitudes and skills in new problematic situations, which will allow him/her to transfer what he/she has learned to new situations. The strategy that was used to get to answer the problem, is the field research; the method used is the quantitative one. We used a population of 69 students and 9 teachers assigned to the Biology, Chemistry and Laboratory Department of the National University of Chimborazo, giving a total of 78 people. As a conclusion, it was obtained that the complexity epistemology influences in the development of transdisciplinary competences in 90.7% (arithmetic mean) in students; and 94.5% (arithmetic mean) in teachers; therefore, it is considered that the complexity epistemology helps to develop transdisciplinary competences in future professionals of the career.